Effects of dietary energy level on antioxidant capability, immune function and rectal microbiota in late gestation donkeys - Guo, Yongmei; Yin, Guolin; Hui, Fang; Guo, Xiaoyu; Shi, Binlin; Zhao, Yanli; Yan, Sumei (Frontiers in Microbiology, 2024)
Introduction This study investigated the effects of dietary energy level on the antioxidant capability, immune function, and rectal microbiota in donkey jennets during the last 60 days of gestation. Methods Fifteen pregnant DeZhou donkeys with age of 6.0 ± 0.1 years, body weight of 292 ± 33 kg, parity of 2.7 ± 0.1 parities and similar expected date of confinement (74 ± 4 days) were randomly allocated to three groups and feed three diets: high energy (10.92 MJ/kg, H), medium energy (10.49 MJ/kg, M), and low energy (9.94 MJ/kg, L). Results and Discussion The serum activity of catalase (CAT), total superoxide dismutase (T-SOD), glutathione peroxidase (GSH-Px), and total antioxidant capacity (T-AOC) in group M was significantly higher, whereas the concentrations of malondialdehyde (MDA), interleukin 1 (IL-1), IL-2, and IL-6 were lower than those recorded for groups H and L (p ≤ 0.05). The dietary energy level significantly affected rectal microbial community structure in the jennet donkeys 35 days and 7 days before the parturition (p ≤ 0.05). The abundances of norank_f_norank_o_Coriobacteriales genus was significantly higher (p ≤ 0.05) in group H, and the abundances of norank_f_norank_o_Mollicutes_RF39 and the Candidatus_Saccharimonas were higher in group L (p ≤ 0.05). The abundance of Fibrobacter in group M was significantly increased (p ≤ 0.05). The abundance of norank_f_norank_o_Coriobacteriales was positively correlated with average daily gain (ADG) and tumor necrosis factor-α (TNF-α) concentrations (p ≤ 0.05). The abundance of norank_f_norank_o_Mollicutes_RF39 was positively correlated with IL-2 and IL-6 concentrations. The abundance of Candidatus_Saccharimonas was positively correlated with CAT, T-SOD and GSH-Px activities (p ≤ 0.05). The abundance of Fibrobacter was positively correlated with CAT and T-SOD activities (p ≤ 0.05), but negatively correlated with IL-2 concentration (p ≤ 0.05). In conclusion, an appropriate dietary with an energy content of 10.49 MJ/kg for jennet donkeys during late gestation increased the prenatal antioxidant capacity, reduced inflammatory cytokines, and promoted fetal growth, and these changes were related to diet-induced changes in rectal microbiota compositions.